European dietitians as key agents of the green transition: An exploratory study of their knowledge, attitudes, practices, and training - Muñoz-Martínez, Júlia; Carrillo-Álvarez, Elena; Janiszewska, Katarzyna (Frontiers in Nutrition, 2023)
Introduction How food systems are currently provisioning food to the population is a matter of debate worldwide. Food systems, driven by widespread and increasing adherence to a westernized dietary pattern, are failing to meet people’s basic needs and are draining natural resources. There is a push to make food systems more healthy, fair, and sustainable. To this end, action from all players is needed to meet the international agenda. In this regard, dietitians play a crucial role, as they can provide advice and promote actions that foster the adoption of more sustainable dietary patterns (SDP) as well as the promotion of sustainable food systems. As an emerging requirement in their training, it is crucial to know what dietitians know about SDP as well as their attitudes and current practices in this field in order to strengthen their competences and be key agents for the green transition. For this reason, the aim of the present study is to explore the knowledge, attitudes, practices, and training (KAPT) of European dietitians on SDP by administering an online survey. Methods Cross-sectional survey administered between April-August 2021 to dietitians based in the European countries with National Dietetic Associations or Education Associate Members affiliated to the European Federation of Associations of Dietitians (EFAD). Results were analyzed based on European region of professional practice (Northern/Southern/Western/South-East Europe), area of expertise and years of experience. Results Responses from 2211 dietitians from 25 countries were received, although the analysis was based on those that responded at least 90% of the survey (n=208). European dietitians are lacking training on SDP but are willing to learn more about it. Most dietitians perceive themselves as able to define an SDP, although aspects concerning social and economic sustainability were underestimated. Dietitians concur that barriers exist to the promotion of SDP, such as the lack of updated national food-based dietary guidelines and the absence of support from peers and managers. The country of professional activity seemed to be key to influencing dietitians’ KAPT. Discussion These results emphasize the need to strengthen European dietitians’ training in SDP and increase public/private commitment to consider dietitians as key professionals for the transition towards SDP.